Cross Docking Study Directed Toward Virtual Screening and Molecular Docking Study of Phenanthrene 1,2,4-triazine Derivatives As Novel Bcl-2 Inhibitors - Mohammad Hasan Jamei; Mehdi khoshneviszadeh; Najmeh Edraki; Maryam Firoozi; Zahra Haghighijoo; Rmin Miri; Amirhossein sakhtaman (Shiraz University of Medical Sciences, 2016)
Apoptosis is critical for tissue homeostasis and for the physiological removal of abnormal cells. Bcl-2 family proteins are important regulators of apoptosis. It's observed that antiapototic Bcl-2 family members are generally over expressed in many cancer cells. As a result, it has stimulated a growing interest in the discovery of small molecules targeting such proteins as potential anticancer therapeutics. With the aim of designing and virtual screening of new phenanthrene based Bcl-2 inhibitors, we performed a cross-docking study. This study is done for different available Bcl-2 X-ray crystal structures in order to find the most appropriate PDB code of this enzyme. After analytical analyses, we found a PDB code for the enzyme. Designed library of phenanthrene triazine containing different hydrazone moieties was further screened using selected crystal structure. It identifies the ligand which interacts the target with lower binding energy. As a conclusion, cross docking study could be a validated strategy for finding the most appropriate crystal structure for docking study. Our designed library of phenanthrene triazine-based derivatives containing hydrazone pendant could be served as potential candidates for Bcl-2 inhibition.